SHOULD LITERARY TEXTS BE USED IN TEACHING AND LEARNING GRAMMAR? - Setya Ariani (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
Traditional grammar teaching focuses mainly on teaching grammar rules directly from textbooks and in return, requiring students to complete a number of activities to demonstrate their understanding and application of such rules. In order to motivate students to be able to express themselves in certain communicative situations, it is also necessary to not only master language rules but also to know the culture of target language. Literary texts are considered effective as authentic materials which can be integrated into foreign language class activities. This article is a literature review that briefly explores the use of literary texts in teaching English grammar. It also shows the practical demonstration of the use of literary texts in grammar class. It is recommended that multiple class activities are designed to incorporate the use of literary texts specifically to improve students’ grammar.